Novel Polysulfone/Carbon Nanotube-Polyamide Thin Film Nanocomposite Membranes with Improved Water Flux for Forward Osmosis Desalination - Rashed, Ahmed O. (ACS Omega, 2020)
[Image: see text] Forward osmosis (FO) is a promising alternative to reverse osmosis (RO) in membrane-based water desalination. In the current study, carboxylated multiwalled carbon nanotubes (MWCNTs) were incorporated in a polyamide (PA) layer formed on top of a polysulfone porous support, resulting in a thin film nanocomposite (TFN) membrane. The amount of MWCNTs was varied (0.01, 0.05, 0.1, and 0.2 wt/vol %). The FO performance was investigated using deionized water as the feed solution and 2 M NaCl as the draw solution. It was found that the carboxylated MWCNTs enhanced the membrane hydrophilicity, surface roughness, and porosity. Such combined effects are believed to have led to enhanced FO water flux. TFN 0.2 showed the highest FO water flux of 73.15 L/m(2) h, an improvement of 67% compared to the blank thin-film composite (TFC) membrane and significantly better than the values reported in the literature. Direct observation by transmission electron microscopy revealed the presence of some open-ended CNTs favorably oriented across the PA layer. Those are believed to have facilitated the transport of water through their inner cores and contributed to the increase in water flux. However, this was at the expense of salt rejection and reverse solute flux performance. The best performing membrane was found to be TFN 0.01. It exhibited a salt rejection of 90.1% with a FO water flux of 50.23 L/m(2) h, which is 13% higher than the TFC membrane, and a reverse solute flux of 2.76 g/m(2) h, which is 21% lower than the TFC membrane. This TFN 0.01 membrane also outperformed the TFN membranes reported in the literature.